2016
DOI: 10.4103/0974-7796.192111
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and prognosis of female acute urinary retention: Analysis of an unusual clinical condition in outpatients

Abstract: Objectives:Acute urinary retention (AUR) in females is a poorly defined condition with undetermined epidemiology. This study aimed to evaluate female AUR in an outpatient population.Patients and Methods:One hundred and thirty-eight adult female outpatients who presented to the emergency room with symptoms of urinary retention were retrospectively analyzed. The women who were ultimately diagnosed with true, complete AUR were systematically reviewed for clinical characteristics and management.Results:In this out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…50% of drug's bioavailability is achieved within two to three hours, since mirtazapine is metabolized through first intestinal and hepatic bypass mechanism. Hence, unlike other antidepressants mirtazapine start therapeutic effect within first week [3]. Male under 48 years, require more dose than female to have equivalent plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…50% of drug's bioavailability is achieved within two to three hours, since mirtazapine is metabolized through first intestinal and hepatic bypass mechanism. Hence, unlike other antidepressants mirtazapine start therapeutic effect within first week [3]. Male under 48 years, require more dose than female to have equivalent plasma concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary retention is not one of the commonly reported side effects, though occasionally it is observed in psychiatry practice [3]. Data available on epidemiology of female urinary retention is also not adequate [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constipation, the use of certain medication and anesthesia appear to be common triggers for female urinary retention and the findings in our series are similar to other studies. [6][7][8] We found that post-operative female urinary retention was common following urogynaecological or general surgical procedures and to a lesser extent post-orthopedic surgery. However, the number of cases in our series was too low to draw any meaningful conclusion about the specific type of surgical procedure itself that increased this risk.…”
Section: Single Retention Episode: Precipitating Factorsmentioning
confidence: 99%
“…Urinary retention in young women is a relatively rare clinical problem. Epidemiological studies estimate that its incidence in young women ranges from 3 cases per 100,000 per year to 0.3% after the exclusion of other causes, such as postoperative, postpartum, gynecological, urological, rectal, and psychiatric causes [ 1 , 2 , 3 ]. The incidence of Fowler’s syndrome is rated at 0.2 cases per 100,000 per year [ 4 ].…”
Section: Introductionmentioning
confidence: 99%